Exploring Textual Metafunction in Selected Nigerian News Reports: Linguistic Description and Interpretation - Koutchadé, Innocent Sourou (Advances in Social Sciences Research Journal, 2017)
This article intends to provide a linguistic analysis of some Nigerian news reports. It is carried out with a view to finding out how news reporters use the language to organize their text so as to convey their message. The paper adopts the textual meaning approach advanced by Halliday (1978; 1985) and detailed by Eggins (2004). Two texts are selected purposely and patterns of Themes and cohesion have been studied. The analyses show that the two texts display high percentage of unmarked topical and textual Themes. Then, both marked Theme and dependent clauses as Themes are less predominant but they are used to draw more attention on some aspects of the message provided. The cohesive analysis has revealed that anaphoric reference chains and features of lexical cohesion have made it easy to understand the meaning conveyed by the two texts. From these analyses, it has been pointed out that the two texts, viewed from their context of production, have accounted for the release of some Chibok girls who were kidnapped by Boko Haram, a terrorist and Islamic group based in the northeastern part of Nigeria, in the year 2014.